Pharmacological and Therapeutic Effects of Vitex agnus‑castus L.: A Review - Niroumand, Mina Cheraghi; Heydarpour, Fatemeh; Farzaei, Mohammad Hosein (Pharmacognosy Reviews)
Vitex agnus‑castus L., known as the chaste tree, is a small deciduous tree which its fruits have been used for more than 2500 years in ancient Egypt, Greece, Iran, and Rome for a variety of gynecologic problems. It has also been used for its claimed activity in the reduction of libido. The German health authorities have approved the use of V. agnus‑castus for menstrual cycle irregularities, premenstrual syndrome, mastalgia, and menopausal disorders. The German Commission E recommended 30–40 mg/day of extract of dried fruit which is standardized based on 0.6% casticin. Scientific studies confirmed several pharmaceutical effects of this medicinal plant including antioxidant, chemopreventive, immunomodulatory and cytotoxicity, tumoricidal, antimutagenic, antimicrobial, antifungal, insect repellant, larvicidal, fracture healing, osteopenic, antinociceptive, opioidergic, antiepileptic, preventing nonalcoholic fat liver disease and oxidative stress, and anti‑inflammatory activities. Adverse effects following by application of this plant are mild and reversible. There are no drug interactions recognized by systematic reviews. Theoretically, chaste tree could interfere with dopaminergic antagonists. In addition, the application of V. agnus‑castus is contraindicated (or should be avoided) during pregnancy due to theoretical opinions and cellular studies that exhibited progesteronic and estrogenic properties of the plant. This study provides the documentation for scientists to use the properties of V. agnus‑castus as an effective herbal medicine and its safety and acceptable dosage are discussed. Advanced preclinical and clinical investigations for sufficiently assessing the safety and therapeutic efficacy of V. agnus‑castus are recommended.
Keywords: Casticin; chaste tree; pharmacological effects; Vitex agnus‑castus